Pengaruh Kualitas Pelayanan terhadap Kepuasan Mahasiswa Universitas Negeri Padang - Abror, Abror (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT The aim of this research is to analyze the service quality and its influence to the student satisfaction in the State University of Padang (UNP). This research used five dimensions of SERVQUAL with the sample of 400 respondents from 27,997 students. With the descriptive analysis, UNP has to improve the service quality to make higher student satisfaction in the future. By using Regression analysis, it is found that five dimensions of SERVQUAL significantly influence the student satisfaction. Partially, only reliability and empathy have significant effect to the student satisfaction. Kata Kunci: Kualitas pelayanan, kepuasan pelanggan, mahasiswa